Magnesia-chrome brick and method for producing the same

CN122667911BActive Publication Date: 2026-10-27DASHIQIAO ZHONGJIAN MAGNESIA BRICK CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611177314.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明的目的在于提供一种镁铬砖及其制备方法,用以解决现有镁铬砖引入纯钛酸铝后高温稳定性差、微裂纹分布无序、长期抗热震性能不足的问题

Benefits of technology

1.本发明通过类质同象取代钛酸铝晶格中的,提高了钛酸铝固溶体在900℃~1300℃区间的热力学稳定性,减少了游离的析出,降低了其与方镁石及窑料中CaO生成低熔点钛酸盐的风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122667911B_ABST
    Figure CN122667911B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of refractory materials, and particularly relates to a magnesite-chrome brick and a preparation method thereof. The method comprises the following steps: first, preparing chromium-doped aluminum titanate solid solution micro powder, mixing the aluminum titanate solid solution micro powder with solid-phase raw materials of the magnesite-chrome brick, adding an organic binder to mix and grind, then treating in an external magnetic field and pressing into a brick blank, and finally drying and high-temperature sintering to obtain a finished product. The application improves the thermodynamic stability of aluminum titanate by isomorphism doping, and narrows the thermal expansion hysteresis loop. Meanwhile, the distribution of the micro powder is regulated by the external magnetic field, and a controllable grain boundary micro-crack network is induced to effectively improve the long-term thermal shock resistance of the magnesite-chrome brick while the basic mechanical properties are retained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory materials technology, specifically relating to a magnesia-chrome brick and its preparation method. Background Technology

[0002] Magnesia-chrome bricks, with periclase as the main crystalline phase, possess the advantages of high temperature resistance and resistance to alkaline slag erosion, and are widely used in the linings of high-temperature industrial kilns such as cement rotary kilns and non-ferrous metal smelting furnaces. The alternating hot and cold conditions caused by frequent start-ups and shutdowns of kilns can easily cause brittle cracks to initiate inside the brick and propagate rapidly, leading to surface spalling, structural failure, and significantly shortening the service life of the bricks.

[0003] To improve the thermal shock resistance of magnesia-chrome bricks, existing technologies often introduce pure aluminum titanate powder into the magnesia-chrome brick system. This relies on the anisotropic expansion characteristics of aluminum titanate crystals to induce microcracks at grain boundaries to dissipate heat stress. However, this approach has significant drawbacks: pure aluminum titanate exhibits thermodynamic instability in the commonly used service range of industrial kilns (900℃–1300℃), easily decomposing into corundum and rutile phases, releasing free... It reacts with MgO and CaO in the magnesia-chrome brick system to form low-melting-point titanates, leading to a decrease in the high-temperature load softening temperature of the brick and a deterioration in its resistance to melting and corrosion. Simultaneously, the large difference in the coefficients of thermal expansion along different axes of pure aluminum titanate crystals results in the formation of large-area thermal expansion hysteresis loops under repeated heating and cooling cycles. Grain boundary microcracks expand disorderly and interconnect with each cycle, causing a rapid decline in the mechanical strength of the brick at room temperature. While the short-term thermal shock resistance is significant, long-term service is prone to large-area spalling, limiting the improvement in service life. More importantly, in conventional molding processes without magnetic field assistance, aluminum titanate micropowder is prone to agglomeration due to its high surface energy. This leads to the local concentration of microcracks within the matrix after firing, evolving into defect sources that damage the brick structure. It is impossible to form a uniform and controlled network stress dissipation structure on a macroscopic scale, making it difficult to effectively block the propagation and penetration of the main cracks. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a magnesia-chrome brick and its preparation method, to solve the problems of poor high-temperature stability, disordered microcrack distribution, and insufficient long-term thermal shock resistance in existing magnesia-chrome bricks after the introduction of pure aluminum titanate. The specific solution is as follows: A method for preparing magnesia-chrome bricks includes the following steps: (1) Preparation of chromium-doped aluminum titanate solid solution micro powder; (2) Take the solid raw material of magnesium chrome brick, add an organic binder and mix evenly to obtain a shaped mixture; the solid raw material of magnesium chrome brick includes the chromium-doped aluminum titanate solid solution micro powder obtained in step (1); (3) The molding mixture is placed in an external magnetic field for magnetization and orientation, and then pressed into brick blanks; (4) The brick blank is dried and then fired at high temperature to obtain the magnesium chrome brick.

[0005] Further, step (1) specifically involves: mixing alumina powder, chromium trioxide powder and titanium dioxide powder, ball milling and then performing solid solution sintering, and then crushing and sieving the sintered product to obtain chromium-doped aluminum titanate solid solution micro powder; the solid solution sintering temperature is 1450℃~1530℃.

[0006] Further, in step (2), the solid raw material of the magnesia-chrome brick is composed of the following components by mass percentage: 55% to 65% magnesia aggregate, 15% to 25% magnesia fine powder, 12% to 20% chromium concentrate micro powder, and 1.5% to 4.5% chromium-doped aluminum titanate solid solution micro powder.

[0007] Furthermore, the main phase of the chromium-doped aluminum titanate solid solution micropowder has the following chemical formula: The solid solution phase.

[0008] Furthermore, the range of x in the general chemical formula is 0.05 ≤ x ≤ 0.35.

[0009] Furthermore, the mass of the solid solution phase accounts for more than 95% of the total mass of the chromium-doped aluminum titanate solid solution micro powder.

[0010] Furthermore, the molar ratio of the alumina powder, chromium trioxide powder, and titanium dioxide powder is: .

[0011] Furthermore, in step (3), the external magnetic field is a directional steady-state magnetic field with a magnetic field strength of 0.5T to 2.0T, and the magnetic field direction is perpendicular to the pressure surface of the brick blank.

[0012] The present invention also provides a magnesium-chrome brick prepared by the above preparation method.

[0013] Compared to existing mixing processes that directly add pure aluminum titanate powder and chromium concentrate powder to the magnesia-chrome brick matrix, the process of pre-preparing chromium-doped aluminum titanate solid solution powder in this invention is fundamentally different, and the core mechanism is as follows: The pre-synthesis process of chromium-doped aluminum titanate solid solution micronized powder is a core and interconnected step in the entire technical solution, and cannot be replaced by a process of directly mixing chromium concentrate micronized powder and pure aluminum titanate micronized powder. In conventional magnesia-chrome brick systems, the chromium trioxide contained in the directly added chromium concentrate micronized powder will preferentially react with the periclase fine powder in the system under the action of thermodynamic driving force during the high-temperature firing stage, forming a magnesia-chrome spinel second phase. If pure aluminum titanate micronized powder is directly added to the system, the powder is prone to lattice instability and decomposition in the temperature range of 900℃ to 1300℃, precipitating free titanium dioxide; in the multiphase matrix system where magnesia and chromium concentrate coexist, the isomorphic solid solution reaction of trivalent chromium ions replacing trivalent aluminum ions cannot be spontaneously completed.

[0014] Meanwhile, pure aluminum titanate lacks paramagnetic properties and cannot respond to an applied magnetic field during molding. This invention utilizes a pre-synthesis process to dissolve trivalent chromium ions with unpaired electrons into the aluminum titanate lattice within a single pure raw material system. This process mitigates the high-temperature decomposition tendency of the powder during service, reducing the probability of low-melting-point titanates forming. Furthermore, it endows the chromium-doped aluminum titanate solid solution micropowder with magnetic anisotropy, enabling magnetization and orientation treatment under an applied magnetic field during molding, thus achieving controllable adjustment of the spatial distribution of microcracks at grain boundaries within the brick.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention is achieved through... Isomorphic substitution in aluminum titanate lattice This improved the thermodynamic stability of aluminum titanate solid solution in the 900℃~1300℃ range and reduced free... The precipitation of these substances reduces the risk of them reacting with periclase and CaO in the kiln feed to form low-melting-point titanates. 2. This invention utilizes... Doping reduces the difference in thermal expansion coefficients across the axes of aluminum titanate crystals, narrowing the thermal expansion hysteresis loop area compared to pure aluminum titanate. Microcracks can partially close during the thermal cycling heating stage, reducing the accumulation of residual stress after multiple cycles and improving the strength retention rate of the brick under long-term thermal shock conditions. 3. This invention introduces an external magnetic field during the molding process. On one hand, when the external magnetic field is a directional steady-state magnetic field, the weak paramagnetism and magnetic anisotropy of the chromium-doped aluminum titanate solid solution micropowder are utilized to achieve preferential particle orientation, inducing the formation of directional, parallel network stress dissipation structures in the grain boundary microcracks during the sintering and cooling period, thus deflecting and absorbing thermal stress. On the other hand, when the external magnetic field is an unsteady alternating magnetic field, the high-frequency vibration generated by the alternating dynamic torque is used to break down powder agglomerates, promoting the uniform dispersion of the chromium-doped aluminum titanate solid solution micropowder in the periclase matrix. Both magnetic field application methods can regulate the spatial distribution of grain boundary microcracks, increasing the long-term thermal shock resistance of the brick without excessively reducing the initial mechanical strength. 4. The raw materials used in this invention are all common materials in the refractory materials industry. Only the pre-synthesis process of chromium-doped aluminum titanate solid solution micro powder is added. The remaining mixing, molding and firing processes are compatible with the existing magnesia-chrome brick production line. The production cost is controllable and it is easy to carry out large-scale production. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0017] Figure 1 This is a process flow diagram of a method for preparing magnesia-chrome bricks according to the present invention; Detailed Implementation The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] In this invention, the external magnetic field refers to an artificially controllable magnetic field constructed within the molding die cavity through a permanent magnet, a DC excitation coil, or an AC excitation device. Based on their time-varying characteristics, magnetic fields can be classified into two categories: steady-state magnetic fields and unsteady-state magnetic fields.

[0019] Magnetization orientation refers to the physical process by which paramagnetic particles, under the influence of an external magnetic field, are driven by magnetic torque to rotate, and their easy magnetization axes are arranged in a preferred orientation along the direction of the magnetic field, thus transforming the random distribution of particles in the matrix into a directional distribution.

[0020] A directional steady-state magnetic field, a type of steady-state magnetic field, refers to a DC magnetic field in which the direction and intensity of the magnetic field do not change with time, and the magnetic field lines have a consistent spatial orientation. In this scheme, it is used to drive the chromium-doped aluminum titanate solid solution micropowder to preferentially orient itself along a direction perpendicular to the pressure surface of the brick blank, inducing the formation of directional grain boundary microcracks during the firing and cooling stage.

[0021] Unsteady magnetic fields (such as alternating magnetic fields) refer to dynamic magnetic fields whose direction and intensity change periodically with time, with alternating magnetic fields being a typical type. In this scheme, the alternating magnetic field causes the chromium-doped aluminum titanate solid solution micropowder to vibrate through periodically reversing magnetic torques, thereby breaking up powder agglomerates and promoting their uniform dispersion in the magnesium-chromium brick matrix.

[0022] Chromium-doped aluminum titanate solid solution micronized powder refers to powder prepared from alumina powder, chromium trioxide powder, and titanium dioxide powder through high-temperature solid solution sintering. Partially replacing aluminum titanate lattice in an isomorphic manner Sites are formed to create single-phase solid solution micropowders with an orthorhombic pseudo-tack tack mineral structure.

[0023] Particle size D 50 The median particle size, also known as the median particle size, refers to the particle size value corresponding to 50% of the cumulative volume distribution in the particle size distribution curve of a powder. It is used to characterize the average particle size level of the powder.

[0024] The magnesia aggregate used in the preparation is selected from at least one of fused magnesia particles and sintered magnesia particles; the chromium concentrate powder is selected from... Industrial chromium ore powder with a mass content ≥45%; alumina powder, chromium trioxide powder, and titanium dioxide powder are all selected from general industrial powders used in the refractory industry; the organic binder can be any one or more of liquid phenolic resin, lignin sulfonate, and polyvinyl alcohol solution, and the amount of organic binder added is 3% to 4% of the total mass of all solid raw materials.

[0025] Example 1 In this embodiment, the solid raw materials for magnesia-chrome bricks are proportioned by mass percentage as follows: 60% magnesia aggregate, 20% magnesia fine powder, 17% chromium concentrate micro powder, and 3% chromium-doped aluminum titanate solid solution micro powder.

[0026] Magnesia aggregate is composed of 1mm-3mm particles and 3mm-5mm particles in a 1:1 mass ratio; the particle size D of the magnesia fine powder is... 50 The particle size D of the chromium concentrate micro powder is 45 μm. 50 It is 38μm.

[0027] The parameters of the chromium-doped aluminum titanate solid solution micro powder are as follows: the molar substitution ratio of chromium at the aluminum site (x) is 0.20; the molar ratio of alumina powder, chromium trioxide powder, and titanium dioxide powder is 0.8:0.2:1; and the particle size D of the chromium-doped aluminum titanate solid solution micro powder is... 50 The particle size is 30 μm, and XRD quantitative phase analysis shows that the mass ratio of the solid solution phase is 96%.

[0028] Preparation steps: (1) Weigh alumina powder, chromium trioxide powder and titanium dioxide powder in a molar ratio of 0.8:0.2:1, mix and ball mill evenly, and perform solid solution sintering at 1490℃. The sintered product is crushed and sieved to obtain a particle size D. 50 Chromium-doped aluminum titanate solid solution micro powder with a diameter of 30 μm; (2) Weigh all the solid raw materials of magnesium chrome bricks, add 3.5% of liquid phenolic resin of the total mass of solid raw materials, and mix thoroughly to obtain the molding mixture; (3) Place the molded mixture in a magnetic field press with a mold, apply a 1.2T directional steady magnetic field with the magnetic field direction perpendicular to the pressing surface of the brick blank, and magnetize and orient the chromium-doped aluminum titanate solid solution micro powder inside the mixture for 3 minutes, so that the easy magnetization axis of the chromium-doped aluminum titanate solid solution micro powder is preferentially oriented along the magnetic field direction; keep the magnetic field energized and press it into a brick blank under a pressure of 180MPa; (4) Dry the brick blank at 110℃ for 18h, then keep it at 1700℃ for 6h and fire it. Cool it to obtain the finished magnesia-chrome brick.

[0029] Example 2 The solid raw material ratio for the magnesia-chrome brick in this embodiment is as follows: 55% magnesia aggregate, 25% magnesia fine powder, 18.5% chromium concentrate powder, and 1.5% chromium-doped aluminum titanate solid solution powder.

[0030] Magnesia aggregate is composed of 1mm-3mm particles and 3mm-5mm particles in a mass ratio of 2:1; the particle size D of magnesia fine powder is... 50 The particle size D of the chromium concentrate micro powder is 42 μm. 50 It is 35μm.

[0031] The parameters of the chromium-doped aluminum titanate solid solution micro powder are as follows: the molar substitution ratio of chromium at the aluminum site, x, is 0.05; the molar ratio of alumina powder, chromium trioxide powder, and titanium dioxide powder is 0.95:0.05:1; the particle size D of the chromium-doped aluminum titanate solid solution micro powder is... 50 The thickness is 45 μm, and the mass percentage of the solid solution phase is 95%.

[0032] The preparation process is the same as in Example 1, except that: In step (1), alumina powder, chromium trioxide powder, and titanium dioxide powder are mixed in a molar ratio of 0.95:0.05:1, and the solid solution sintering temperature is 1450℃; in step (2), the amount of liquid phenolic resin is 3% of the total mass of the solid raw materials; in step (3), the directional steady-state magnetic field strength is 0.5T, and the molding pressure is 150MPa; in step (4), the drying regime is drying at 100℃ for 24h, and the firing regime is holding at 1680℃ for 8h.

[0033] Example 3 The solid raw material ratio for the magnesia-chrome brick in this embodiment is as follows: 65% magnesia aggregate, 15% magnesia fine powder, 15.5% chromium concentrate powder, and 4.5% chromium-doped aluminum titanate solid solution powder.

[0034] Magnesia aggregate is composed of a gradation mixture of 1mm-3mm and 3mm-5mm particles at a mass ratio of 1:2; the particle size D of the magnesia fine powder is... 50 The particle size D of the chromium concentrate micro powder is 48 μm. 50 It is 40μm.

[0035] The parameters of the chromium-doped aluminum titanate solid solution micro powder are as follows: the molar substitution ratio of chromium at the aluminum site (x) is 0.35; the molar ratio of alumina powder, chromium trioxide powder, and titanium dioxide powder is 0.65:0.35:1; and the particle size D of the chromium-doped aluminum titanate solid solution micro powder is... 50 The thickness is 15 μm, and the mass percentage of the solid solution phase is 95%.

[0036] The preparation process is the same as in Example 1, except that: In step (1), alumina powder, chromium trioxide powder, and titanium dioxide powder are mixed in a molar ratio of 0.65:0.35:1, and the solid solution sintering temperature is 1530℃; in step (2), the amount of liquid phenolic resin is 4% of the total mass of the solid raw materials; in step (3), the directional steady-state magnetic field strength is 2.0T, and the molding pressure is 200MPa; in step (4), the drying regime is drying at 120℃ for 12h, and the firing regime is holding at 1730℃ for 4h.

[0037] Example 4 The solid phase raw material ratio of the magnesia-chrome brick in this embodiment is the same as that in Example 1.

[0038] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0039] The doping parameters for the chromium-doped aluminum titanate solid solution micropowder are the same as in Example 1, except that the particle size D of the chromium-doped aluminum titanate solid solution micropowder is... 50 It is 40μm.

[0040] The preparation process is the same as in Example 1.

[0041] Example 5 The solid phase raw material ratio of the magnesia-chrome brick in this embodiment is the same as that in Example 1.

[0042] The particle size parameters of the solid raw materials for magnesia-chrome bricks are as described in Example 1.

[0043] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0044] The preparation process is the same as in Example 1, except that the directional steady-state magnetic field strength in step (3) is 1.0T.

[0045] Example 6 The solid phase raw material ratio of the magnesia-chrome brick in this embodiment is the same as that in Example 1.

[0046] The particle size parameters of the solid raw materials for magnesia-chrome bricks are as described in Example 1.

[0047] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0048] The preparation process is the same as in Example 1, except that: in step (3), the shaped mixture is placed in a magnetic field press with a mold, without applying a directional steady magnetic field, and an alternating current is passed through to form an alternating unsteady magnetic field with a working frequency of 50Hz and a peak magnetic field strength of 1.2T. The alternating magnetic torque is used to complete the magnetization orientation of the chromium doped aluminum titanate solid solution micro powder and the agglomeration of the crushed particles. The processing time is 3min. The alternating magnetic field is kept in the energized state and pressed into a brick blank with a pressure of 180MPa.

[0049] Comparative Example 1 The solid raw material ratio of this comparative magnesia-chrome brick is: 63% magnesia aggregate, 20% magnesia fine powder, and 17% chromium concentrate powder, without adding chromium-doped aluminum titanate solid solution powder.

[0050] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0051] The preparation process is the same as in Example 1, except that: no chromium-doped aluminum titanate solid solution micro powder is prepared, and the remaining solid raw materials are directly weighed and mixed; in step (3), no external magnetic field is applied during the molding process, and the brick blank is directly pressed into a brick blank with a pressure of 180MPa.

[0052] Comparative Example 2 The solid raw material ratio for magnesia-chrome bricks is the same as in Example 1, except that: the chromium-doped aluminum titanate solid solution micro powder is replaced with an equal mass of pure aluminum titanate micro powder, and the particle size D of the pure aluminum titanate micro powder is... 50 It is 30μm.

[0053] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0054] The preparation process is the same as in Example 1.

[0055] Comparative Example 3 The solid raw material ratio for magnesia-chrome bricks is as described in Example 1.

[0056] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0057] The doping parameters for the chromium-doped aluminum titanate solid solution micropowder are the same as in Example 1, except that: the molar substitution ratio x of chromium at the aluminum site is 0.02; the molar ratio of alumina powder, chromium trioxide powder, and titanium dioxide powder is 0.98:0.02:1; and the particle size D of the chromium-doped aluminum titanate solid solution micropowder is... 50 The thickness is 30 μm, and the mass percentage of the solid solution phase is 92%.

[0058] The preparation process is the same as in Example 1, except that the solution sintering temperature in step (1) is 1450℃.

[0059] Comparative Example 4 The solid raw material ratio for magnesia-chrome bricks is as described in Example 1.

[0060] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0061] The doping parameters for the chromium-doped aluminum titanate solid solution micropowder are the same as in Example 1, except that: the molar substitution ratio x of chromium at the aluminum site is 0.40; the molar ratio of alumina powder, chromium trioxide powder, and titanium dioxide powder is 0.60:0.40:1; and the particle size D of the chromium-doped aluminum titanate solid solution micropowder is... 50 The thickness is 30 μm, and the mass percentage of the solid solution phase is 78%.

[0062] The preparation process is the same as in Example 1, except that the solution sintering temperature in step (1) is 1530℃.

[0063] Comparative Example 5 The solid raw material ratio for magnesia-chrome bricks is as described in Example 1.

[0064] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0065] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0066] The preparation process is the same as in Example 1, except that in step (3), the external magnetic field is turned off and the brick blank is directly pressed into a conventional pressure of 180MPa.

[0067] Comparative Example 6 The solid raw material ratio for magnesia-chrome bricks is the same as in Example 1, except that: 0.8% of chromium-doped aluminum titanate solid solution micro powder and 22.2% of magnesia fine powder are used.

[0068] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0069] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0070] The preparation process is the same as in Example 1.

[0071] Comparative Example 7 The solid raw material ratio for magnesia-chrome bricks is the same as in Example 1, except that: 6.0% of chromium-doped aluminum titanate solid solution micro powder and 17% of magnesia fine powder are used.

[0072] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0073] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0074] The preparation process is the same as in Example 1.

[0075] Comparative Example 8 The solid raw material ratio for magnesia-chrome bricks is the same as in Example 1, except that: 29% fine magnesia powder and 8.0% chromium concentrate powder.

[0076] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0077] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0078] The preparation process is the same as in Example 1.

[0079] Comparative Example 9 The solid raw material ratio for magnesia-chrome bricks is the same as in Example 1, except that: 9.0% is fine magnesia powder and 28% is chromium concentrate powder.

[0080] The particle size of the solid raw material for magnesia-chrome bricks is as described in Example 1.

[0081] The doping parameters for chromium-doped aluminum titanate solid solution micropowder are as described in Example 1.

[0082] The preparation process is the same as in Example 1.

[0083] Table 1 Summary of Performance Comparison between Each Example and Comparative Example Note: In Comparative Example 2, "3.0% (pure)" indicates that the added substance is pure aluminum titanate powder, not chromium-doped aluminum titanate solid solution powder, and its addition amount is 3.0% of the total mass of solid raw materials.

[0084] Testing standards and methods Initial room temperature compressive strength: All specimens were processed and loaded according to the procedures specified in GB / T 5072-2008 "Test Method for Room Temperature Compressive Strength of Refractory Materials". Each group of parallel specimens shall have no less than 5 specimens, and the arithmetic mean shall be taken as the final test value.

[0085] Thermal shock water cooling test: A uniform cycle of 1100℃ for 30 min followed by immersion in water at room temperature for 5 min was adopted. After each cycle, the surface cracks and spalling of the specimen were observed. The number of cycles in which large-area macroscopic spalling or through-cracks appeared on the specimen was taken as the failure thermal shock cycle number. Specimens that did not show macroscopic spalling after 15 cycles were tested again for room temperature compressive strength, and the strength retention rate was calculated.

[0086] Powder phase and particle size analysis: Chromium-doped aluminum titanate solid solution micronized powder was crushed and sampled. The proportion of the target solid solution phase was quantitatively calculated using XRD patterns combined with the K-value method. Powder particle size was measured using a wet laser particle size analyzer. 50 Particle size characteristic parameters.

[0087] Characterization of hysteresis loop area for thermal expansion: Take a sample of chromium-doped aluminum titanate solid solution micro powder, heat it from room temperature to 1400℃ and then cool it down to room temperature at 10℃ / min on a thermal expansion instrument, record the heating and cooling curves, calculate the hysteresis loop area, and calculate the relative ratio value with the hysteresis loop area of ​​pure aluminum titanate powder of the same particle size as the benchmark (100%).

[0088] Bulk density and apparent porosity testing: The bulk density and apparent porosity of the sintered and shaped products were determined in accordance with GB / T 2997-2015.

[0089] Based on the test data in Table 1, the following analysis is conducted, taking into account the formulation composition, phase structure, and preparation process: In Examples 1-6 of this invention, the introduction of chromium-doped aluminum titanate solid solution micropowder resulted in the formation of uniformly distributed grain boundary microcracks within the matrix due to thermal mismatch during the sintering and cooling process. These microcracks caused a slight decrease in the initial room-temperature compressive strength of the product. The initial strength range of Examples 1-5 was 63-67 MPa, which is lower than that of Comparative Example 1 (72 MPa), which did not contain chromium-doped aluminum titanate solid solution micropowder and was not subjected to an external magnetic field. This phenomenon is a normal expected result of the microcrack toughening design. Comparative Example 1 had a dense matrix structure but lacked a microcrack network that could dissipate heat dissipation stress. It experienced large-area spalling after 8 thermal cycles, and the strength retention rate was only 13% after 15 water cooling cycles. Examples 1-5, relying on the directional arrangement of grain boundary microcracks to deflect and buffer thermal stress, achieved a strength retention rate of 65%-75% after 15 water cooling cycles, and the number of failure thermal shock cycles was increased to 29-39.

[0090] Comparing the samples of Example 1 and Comparative Example 5, which had identical amounts of chromium-doped aluminum titanate solid solution micropowder and doping parameters, with the only difference being whether a magnetic field was applied during the molding stage, it can be seen that directional steady-state magnetic field molding can improve the long-term thermal shock resistance of the products. Chromium-doped aluminum titanate solid solution micropowder possesses magnetic anisotropy. After magnetization and orientation treatment by the directional steady-state magnetic field, the chromium-doped aluminum titanate solid solution micropowder is arranged in an orderly manner along the direction of the magnetic field within the brick blank. After firing, the grain boundary microcracks are distributed in a parallel directional network, which can orderly dissipate heat dissipation shear stress and inhibit crack cross-penetration. In Comparative Example 5, which was molded without a magnetic field, the chromium-doped aluminum titanate solid solution micropowder is randomly distributed, and the microcracks are disorderly interwoven. The failure thermal shock cycle count is 21, and the strength retention rate after 15 water cooling cycles is 54%, both of which are lower than those of Example 1. Meanwhile, comparing the samples with completely identical raw material formulations and chromium-doped aluminum titanate solid solution micro powder parameters in Example 1 (1.2T) and Example 5 (1.0T), it can be seen that under the premise of strictly controlling a single variable, reducing only the directional steady-state magnetic field strength during the molding stage results in a corresponding decrease in the number of thermal shock cycles of the product (from 36 to 34). It can be seen that there is a clear positive correlation between the directional steady-state magnetic field strength and the thermal shock resistance of the product.

[0091] Combining the performance data from the two boundary verification examples, Example 2 (0.5T) and Example 3 (2.0T), it can be further found that: although the raw material ratio and the particle size of the chromium-doped aluminum titanate solid solution micropowder were adjusted, under their respective parameter systems, the higher the applied directional steady-state magnetic field strength, the more conducive it is to driving the weakly paramagnetic chromium-doped aluminum titanate solid solution micropowder to overcome spatial frictional resistance and complete the preferred orientation arrangement (magnetized orientation); the failure thermal shock cycle number of the sample after firing also showed a stepwise change with the increase of magnetic field strength (from 29 times to 39 times). In addition, the mass ratio of the solid solution phase in the samples of the above examples was consistently maintained above 95%, and the corresponding thermal expansion hysteresis ring relative area showed a narrowing evolution law with the increase of the molding magnetic field strength. This phase structure change can illustrate that the magnetized orientation control mechanism of the present invention has the scope of application and theoretical rationality.

[0092] Example 6 uses a 50Hz alternating unsteady magnetic field for molding. While it lacks one-dimensional directional arrangement, the high-frequency reversal of the alternating magnetic field generates shear oscillations, breaking up particle agglomeration and achieving a three-dimensional uniform dispersion of chromium-doped aluminum titanate solid solution micropowder within the matrix. Test data shows that Example 6 has a failure thermal shock cycle count of 27 cycles and a water-cooling strength retention rate of 61% after 15 cycles, both higher than Comparative Example 5 which was molded without a magnetic field. These results indicate that the applied magnetic field is not limited to a directional steady-state magnetic field; alternating unsteady magnetic fields can also improve the structure of the brick and enhance its thermal shock resistance.

[0093] Compared to Comparative Example 2 with added pure aluminum titanate powder and Comparative Example 3 with low doping (x=0.02), the relative areas of the thermal expansion hysteresis loops were 100% and 92%, respectively. During thermal cycling, the degree of microcrack closure was limited, residual stress continued to accumulate, and the strength retention rate after 15 water cooling cycles was only 29% and 33%, respectively, with only 14 and 15 failure cycles. Examples 1-3 controlled the chromium substitution ratio (x) within the range of 0.05-0.35, using... The modulation of lattice distortion in aluminum titanate narrowed the relative area of ​​the hysteresis ring to 28%–42%, improving the strength retention after thermal shock. In the comparative example, a x value of 0.40 exceeded the isomorphic solid solution limit, resulting in the precipitation of a large amount of impurity phases and an initial room-temperature compressive strength of only 55 MPa. This indicates that a x value of 0.05–0.35 is a reasonable range that balances phase purity and thermal shock performance.

[0094] In Comparative Example 6, the addition amount of chromium-doped aluminum titanate solid solution micropowder was 0.8%, resulting in a low microcrack density and an inability to form continuous stress release channels, with a failure cycle count of only 10. In Comparative Example 7, the addition amount of chromium-doped aluminum titanate solid solution micropowder was 6.0%, with excessive microcracks damaging the matrix skeleton structure, reducing the initial strength to 48 MPa, and the failure cycle count was only 16. In Examples 1-5, the addition amount of chromium-doped aluminum titanate solid solution micropowder was controlled within the range of 1.5% to 4.5%, achieving a balance between mechanical strength and thermal shock resistance, with the failure thermal shock cycle count consistently maintained above 29.

[0095] To verify the effect of the chromium concentrate powder dosage range on the product performance, comparative examples 8 and 9 were set up to conduct boundary verification, while keeping the amount of magnesia solid raw material and the amount of chromium-doped aluminum titanate solid solution powder constant: when the chromium concentrate powder dosage was 8.0% and the magnesia fine powder dosage was adjusted to 29.0% (comparative example 8), the amount of chromium concentrate powder provided by the brick matrix was... Insufficient component content makes it difficult to form a continuously distributed spinel bonding phase at the grain boundaries of the periclase main crystal phase during high-temperature sintering, resulting in a decrease in the internal chemical bonding strength of the brick. The initial room temperature compressive strength is 51 MPa, and the failure thermal shock cycle count is 17. When the content of chromium concentrate micro powder is 28.0% and the content of magnesia fine powder is adjusted to 9.0% (Comparative Example 9), the content of active MgO component provided by magnesia fine powder in the brick matrix is ​​insufficient. The spinel formation reaction is uneven during sintering, resulting in a large number of disordered voids inside and a loose matrix structure. The initial room temperature compressive strength is 44 MPa, and the failure thermal shock cycle count is 18. The data from the two sets of boundary samples indicate that when the content of chromium concentrate micro powder deviates from the range of 12% to 20%, both the mechanical properties and thermal shock resistance of the product decrease.

[0096] The results above show that controlling the molar substitution ratio x of chromium at the aluminum site to 0.05–0.35, the amount of chromium concentrate powder to 12%–20%, the amount of chromium-doped aluminum titanate solid solution powder to 1.5%–4.5%, and applying an external magnetic field of 0.5T–2.0T (either directional steady state or alternating unsteady state) during the molding stage can effectively narrow the thermal expansion hysteresis loop and improve the strength retention rate and anti-stripping cycle number under long-term hot and cold cycling conditions while preserving the basic mechanical properties of the product.

[0097] The above description of the disclosed embodiments enables those skilled in the art to make or use this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing magnesia-chrome bricks, characterized in that, Includes the following steps: (1) Preparation of chromium-doped aluminum titanate solid solution micro powder; (2) Take the solid raw material of magnesium chrome brick, add an organic binder and mix evenly to obtain a shaped mixture; the solid raw material of magnesium chrome brick includes the chromium-doped aluminum titanate solid solution micro powder obtained in step (1); (3) The molding mixture is placed in an external magnetic field for magnetization and orientation, and then pressed into brick blanks; (4) The brick blank is dried and then fired at high temperature to obtain the magnesium chrome brick; Step (1) specifically involves: mixing alumina powder, chromium trioxide powder and titanium dioxide powder, ball milling and then performing solid solution sintering. The resulting sintered product is crushed and sieved to obtain chromium-doped aluminum titanate solid solution micro powder. The solid solution sintering temperature is 1450℃~1530℃. In step (2), the solid raw material of the magnesia-chrome brick is composed of the following components by mass percentage: 55%–65% magnesia aggregate, 15%–25% magnesia fine powder, 12%–20% chromium concentrate micro powder, and 1.5%–4.5% chromium-doped aluminum titanate solid solution micro powder; The main phase of the chromium-doped aluminum titanate solid solution micropowder has the following general chemical formula: The solid solution phase; In the general chemical formula, the value of x is in the range of 0.05 ≤ x ≤ 0.35; The mass of the solid solution phase accounts for more than 95% of the total mass of the chromium-doped aluminum titanate solid solution micro powder.

2. The preparation method according to claim 1, characterized in that, The molar ratio of the alumina powder, chromium trioxide powder, and titanium dioxide powder is: .

3. The preparation method according to claim 2, characterized in that, In step (3), the external magnetic field is a directional steady-state magnetic field with a magnetic field strength of 0.5T to 2.0T and the magnetic field direction is perpendicular to the pressure surface of the brick blank.

4. A magnesium chrome brick prepared by the preparation method according to any one of claims 1-3.

Citation Information

Patent Citations

  • Preparation method for magnesium-chromium refractory material

    CN110590385A

  • Magnetisable abrasive particles and methods of making same

    CN114556497A